1979
DOI: 10.1007/bf01556107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal failure on gastrointestinal hormones

Abstract: The development of sensitive, specific radioimmunoassays has enabled study of gastrointestinal hormones in various disease states. Since the findings that the kidney catabolizes gastrin and serum gastrin is elevated in chronic renal failure and in anephric patients, other hormones have been studied in these conditions. Cholecystokinin (CCK), GIP, glucagon, and secretin are all elevated in chronic renal failure and the degree of elevation is correlated with the severity of renal impairment. Hemodialysis leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1979
1979
1998
1998

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Complete cessation of renal function after bilateral nephrectomy leads to elevated levels of a number of gastrointestinal hormones (Hansky 1979). Bilateral nephrectomy, as employed in the C. Post, unpublished data).…”
Section: Discussionmentioning
confidence: 95%
“…Complete cessation of renal function after bilateral nephrectomy leads to elevated levels of a number of gastrointestinal hormones (Hansky 1979). Bilateral nephrectomy, as employed in the C. Post, unpublished data).…”
Section: Discussionmentioning
confidence: 95%
“…In a study on a large number of patients, it has been shown that the serum gastrin rises proportionally with the serum creatinine, the higher the creatinine, the higher the gastrin. The relationships of this increase in gastrin to acid secretion and peptic ulceration in this group ofpatients with chronic renal failure is not clear as most patients do not have ulcer problems (Hansky, 1979).…”
Section: Chronic Renalfailurementioning
confidence: 89%
“…In spite of the fact that there are considerable differences in the CCK B receptor expression depending on the species that were studied (Reubi et al 1997b), it seems reasonable to examine the presence of CCK B receptor and effects of gastrin also in the human kidney. Serum gastrin levels are high even in early stages of chronic renal failure (Hansky 1979), offering the possibility that gastrin and related hormones are involved in the structural remodelling of the kidney during the progression of renal disease (Wolf and Nielsen 1991). These potential effects of gastrin could also be of importance in other frequent conditions in which hypergastrinemia is observed such as Helicobacter pylori infection of the gastric mucosa (Graham et al 1991;Calam et al 1997) or during the therapeutically achieved suppression of gastric acid secretion (Sundler et al 1986;Lamberts 1993).…”
Section: Discussionmentioning
confidence: 99%